LEADERSHIP CHARACTERISTICS OF MUSLIM WARD HEAD IN NURSING CARE - Muhammad Basirun (Multidisciplinary Indonesian Center Journal (MICJO), 2026)
Background: The position of ward head is crucial because their managerial skills play a significant role in the success of nursing services. The leader's character contributes optimally to creating quality nursing care. The results of this study are crucial because they discuss appropriate leadership characteristics in managing nursing wards. The past leadership characteristics of the Prophet Muhammad (peace be upon him) serve as the basis for patient management. The purpose of this study was to conduct a literature review related to the leadership characteristics of Muslim ward heads, based on the leadership characteristics of the Prophet Muhammad (peace be upon him). The research method was a literature review of Islamic leadership character theories. The results revealed that the leadership characteristics of the best Muslim ward heads in nursing care are honesty, trustworthiness, intelligence, fairness, preaching, responsibility, discipline, initiative, being a role model, and providing inspiration. Conclusion: The leadership characteristics of Muslim ward heads are the foundation of good conventional leadership characteristics that can be implemented in managing patient nursing care.